Rainfall changes perceived by farmers and captured by meteorological data: Two sides to every story - Lena Hubertus; Juliane Groth; Mike Teucher; Kathleen Hermans (Regional Environmental Change, 2023)
Subsistence farmers with high dependency on natural resources are exceptionally vulnerable to rainfall changes. Besides, they are in the front row when it comes to observing these changes. Studies that systematically investigate similarities and differences between measured and perceived rainfall changes are typically limited to trends in rainfall amounts, thereby disregarding changes in extreme events, rainy season durations, and timing. We address this gap by contrasting rainfall changes perceived by subsistence farmers in the Ethiopian highlands with meteorological daily rainfall data derived from the Climate Hazards Group Infrared Precipitation with Stations (CHIRPS). We applied nine distinct metrics for rainfall dynamics, accounting for rainfall variability, including extreme events and changes in the onset and cessation of the two rainy seasons. Farmers perceived increasingly unreliable rainfall for both the short and the long rainy seasons, with later onset and earlier cessation, increasing rainfall intensity, and increasing occurrence of untimely rainfall and droughts. This partially disagrees with the CHIRPS data that indicate most significant rainfall changes for the short rainy season only. Since the early 1980s, this season has been experiencing decreasing rainfall amounts, with high variability between years and an increasingly uncertain – yet delayed – onset. In contrast, the long rainy season experienced little changes in rainfall. Our results point towards changing farmers' water availability and water demand as an explanation for the perceived deteriorating rainfall conditions. As farmers' perceptions partly diverge from meteorological observations, both data sources should be used complementarily to improve our understanding of climatic change.
Keywords: 320; rainfall changes; perceptions; meteorological data; CHIRPS; Ethiopian highlands